Pengaruh Fasilitas, Kualitas Pelayanan Dan Harga Terhadap Kepuasan Pelanggan: (Studi Kasus Solo’s Bistro) - I Gede Januarsa; Asnawi Hidayat (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2025)
This study aims to determine and analyze the direct effect of Facilities on Customer Satisfaction at Solo's Bistro, to determine and analyze the direct effect of Service Quality on Customer Satisfaction at Solo's Bistro, to determine and analyze the direct effect of Price on Customer Satisfaction at Solo's Bistro and to determine and analyze the simultaneous effect of Facilities, Service Quality, Price on Customer Satisfaction at Solo's Bistro. This study uses a quantitative method with a sample size of 100 customer respondents at Solo's Bistro. Data were analyzed using validity tests, reliability tests, multicollinearity tests, heteroscedasticity tests, normality tests, multiple linear regression analysis tests, T tests, F tests, R2 determination coefficient tests using IBM SPSS Statistics. The results of the study show that directly Facilities have a significant effect on Customer Satisfaction in Solo's Bistro customers, directly Price has a significant effect on Customer Satisfaction in Solo's Bistro customers, directly Service Quality has a significant effect on Customer Satisfaction in Solo's Bistro customers, and directly and simultaneously Facilities, Service Quality, and Price have a significant effect on Customer Satisfaction in Solo's Bistro customers.